Teknologi Digital: Pendorong Utama Pertumbuhan Ekonomi Indonesia - Maghfiroh, Alifia Nisa (Maliki Interdisciplinary Journal, 2023)
The role of digital technology as a driver of Indonesian’s economic growth is increasingly important. The application of digital technology has penetrated several economic sectors. This leads to significant efficiency and productivity and creates new jobs. The growth of e-commerce and financial technology (fintech) has changed the way people shop and conduct financial transactions in Indonesian. More and more business people, especially UMKM’s, can use digital platforms to expand their market reach, contributing to local economic growth. In the agricultural sector, digital technology plays an important role in more efficient use of resources, such as sensor-based irrigation and drone-based agricultural monitoring. Creative industry actors can use the Internet and other digital technologies to market their creations worldwide, creating added value for Indonesian. While the development of digital technology shows great potential, the challenges are also significant, such as implementing Indonesian’s evenly distributed technology infrastructure, protecting personal information and improving the skills of technology workers. However, with the commitment and cooperation of all parties, digital technology can continue to be a key driver of Indonesian’s economic growth.